Mesozoic tectonic regime transformation in Fujian Province (Southeast China): Evidence from palaeostress field restoration and lithofacies palaeogeography evolution - Tan, Yuanlong; Wang, Zongxiu; Li, Chunlin; Yan, Xili; Peng, Nan (Geological journal (Chichester, England), 2024)
The South China region has undergone a complex tectonic history since the Mesozoic era, characterized by significant tectonic regime transformations. However, the mechanism behind these transformations is still subject to debate. This study aims to elucidate the specific manifestations and stress mechanisms driving the tectonic transformations and their geological background. Through field geological surveys, effective stress inversions and analysis of lithofacies palaeogeography in Fujian Province, we have identified six distinct tectonic episodes that occurred during the Mesozoic: (a) late Middle Triassic to early Late Triassic: intense NNE–SSW compression generated an unconformity between the An'ren Formation and Dakeng Formation; (b) middle Late Triassic to early Middle Jurassic: NNE–SSW extension exerted control over the deposition of the Dakeng Formation, Wenbinshan Formation and Zhangping Formation; (c) late Middle Jurassic to early Late Jurassic: NW–SE compression resulted in an unconformity between the Zhangping Formation and Changlin Formation; (d) late Jurassic to early Cretaceous: NW–SE extension influenced the deposition of the Changlin Formation, Nanyuan Formation and Xiaoxi Formation; (e) late Early Cretaceous to Late Cretaceous: a strike–slip stress field caused an unconformity between the Xiaoxi Formation and Shaxian Formation; (f) post‐Late Cretaceous: NE–SW extension occurred. During the late Middle Jurassic to early Late Jurassic period, there was a notable change in the distribution of lithofacies palaeogeography. The coexistence of NE and E‐W‐trending patterns shifted to a predominant NE‐trending pattern, which was controlled by the palaeostress field transitioning from NNE–SSW extension to NW–SE compression. These changes indicate a tectonic regime transformation in Southeast China during this period. Considering the sedimentary, magmatic and tectonic activities, the tectonic evolution of Southeast China was predominantly influenced by the Palaeo‐Tethys tectonic domain from the Early Triassic to early Middle Jurassic and by the Palaeo‐Pacific tectonic domain from the late Middle Jurassic to the Cretaceous. The tectonic setting analysis results from sedimentary characteristics and lithofacies palaeogeography were in good coordination with palaeostress regime. Tectonic regime transformation in eastern South China happened in the late Middle Jurassic to early Late Jurassic.